2020
DOI: 10.2174/1381612826666200114100553
|View full text |Cite
|
Sign up to set email alerts
|

Burden and Prevention of HPV. Knowledge, Practices and Attitude Assessment Among Pre-Adolescents and their Parents in Italy

Abstract: Despite infections due to HPV nowadays represent the most common sexually transmitted diseases worldwide with recognized effective and safe preventive strategies, knowledge, attitudes; however, awareness on HPV is considerably low. The present study has two main objectives: 1. To conduct a literature review to analyze the evolution of preventive tools, the complexity of the vaccine choice process, and the challenges posed by HPV vaccine hesitancy and refusal among pre-adolescents and their parents; 2. To asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 73 publications
2
12
1
5
Order By: Relevance
“…To address this criticism, in May 2017, the World Health Organization (WHO) highlighted the relevance of cervical cancer and other HPV-related diseases as a global public health threat, and conformed the recommendation to include HPV vaccines into national immunization programs as part of a coordinated and comprehensive strategy to prevent HPV-related diseases [10]. The successful implementation of primary prevention of HPV infection is based on an integrated approach that includes the analysis and management of organizational aspects of immunization campaigns and raising awareness among the general population and high-risk subjects [11][12][13][14][15][16]. This requires active involvement by the healthcare workers, who play a key role in promoting the HPV vaccination and its acceptability, since they can influence the whole health behavior of their patients.…”
Section: Introductionmentioning
confidence: 91%
“…To address this criticism, in May 2017, the World Health Organization (WHO) highlighted the relevance of cervical cancer and other HPV-related diseases as a global public health threat, and conformed the recommendation to include HPV vaccines into national immunization programs as part of a coordinated and comprehensive strategy to prevent HPV-related diseases [10]. The successful implementation of primary prevention of HPV infection is based on an integrated approach that includes the analysis and management of organizational aspects of immunization campaigns and raising awareness among the general population and high-risk subjects [11][12][13][14][15][16]. This requires active involvement by the healthcare workers, who play a key role in promoting the HPV vaccination and its acceptability, since they can influence the whole health behavior of their patients.…”
Section: Introductionmentioning
confidence: 91%
“…In fact, in the early HIV epidemic, higher HIV infections were found among more educated people [ 14 , 15 ], while more recent studies indicated that education acted as a social vaccine against HIV risk [ 16 , 17 ]. Worldwide, numerous scientists assessed the level of knowledge about these infections among students of different ages and attending different types of schools and universities [ 6 , 12 , 18 , 19 ], while others evaluated the impact of STDs educational interventions [ 1 , 20 , 21 , 22 , 23 , 24 ]. An interesting theoretical framework employed in prevention programs regarding both STDs infections and other health-related risks is based on exploring “knowledge”, “information needs”, and “risk perception” [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…A multicenter project coordinated by the Department of Health Sciences of the University of Genoa was conducted in four Italian Regions (Liguria, Veneto, Apulia, Sicily) with the main objective being to evaluate the offer of vaccination, coverage rates, and determinants associated with HPV vaccination uptake or refusal in different age classes and target groups [ 13 , 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%